Long-term follow-up of post-cardiac surgery Mycobacterium chimaera infections: A 5-center case series. Issue 2 (February 2020) - Julian, Kathleen G.; Crook, Tonya; Curley, Eugene; Appenheimer, A. Ben; Paules, Catharine I.; Hasse, Barbara; Diekema, Daniel J.; Daley, Charles L.; de Sanctis, Jorgelina; Hellinger, Walter C.; Levin, Adrah; McSherry, George; et al.
Highlights: Indolent symptoms of endovascular M. chimaera do not portend a benign course. Despite antimicrobials, mortality was high for post-surgery patients with M. chimaera. Relapses of M. chimaera may also manifest minimal or indolent symptoms. Only 3 of 12 with infected, retained cardiac prosthesis achieved control of infection. This infection warrants aggressive treatment and long-term monitoring. Abstract: Objectives: In multiple countries, endovascular/disseminated Mycobacterium chimaera infections have occurred in post-cardiac surgery patients in association with contaminated, widely-distributed cardiac bypass heater-cooler devices. To contribute to long-term characterization of this recently recognized infection, we describe the clinical course of 28 patients with 3–7 years of follow-up for survivors. Methods: Identified at five hospitals in the United States 2010–2016, post-cardiac surgery patients in the cohort had growth of Mycobacterium avium complex (MAC)/ M. chimaera from a sterile site or surgical wound, or a clinically compatible febrile illness with granulomatous inflammation on biopsy. Case follow-up was conducted in May 2019. Results: Of 28 patients, infection appeared to be localized to the sternum in four patients. Among 18 with endovascular/disseminated infection who received combination anti-mycobacterial treatment and had sufficient follow-up, 39% appeared to have controlled infection (>12 months), 56% died, and one patient is alive with relapsed bacteremia. While the number of patients is small and interpretation is limited, four (67%) of six patients who had cardiac prosthesis removal/replacement appeared to have controlled infection compared to three (25%) of 12 with retained cardiac prosthesis ( p >0.14; Fisher's exact test). Conclusions: Given poor response to treatment and potential for delayed relapses, post-cardiac surgery M. chimaera infection warrants aggressive treatment and long-term monitoring.